Our evenings : a novel - Hollinghurst, Alan (Random House, 2024)
"This piercing novel from "one of our most gifted writers" (The Boston Globe) is a portrait of modern England through the lens of one man's acutely observed and often unnerving experience, as he struggles with race and class, art and sexuality, love and the cruel shock of violence. Did I have a grievance? Most of us, without looking far, could find something that had harmed us, and oppressed us, and unfairly held us back. I tried not to dwell on it, thought it healthier not to, though I'd lived my short life so far in a chaos of privilege and prejudice. Dave Win is thirteen years old in 1961, when he first goes to stay with the wealthy Hadlows, who sponsor his scholarship at a boarding school where their son Giles is his classmate. This weekend of board games with complicated rules, multicourse meals, and conversation about theater and modern art--so different from the quiet life he and his mother share in their small apartment--opens up heady new possibilities for Dave, even as it exposes him to Giles's envy and brutality. As Our Evenings unfolds over the next sixty years, the two boys' lives will diverge dramatically, Dave a talented actor, whose queerness and Burmese heritage move him in and out of the margins, Giles an increasingly powerful and dangerous right-wing politician. This novel is Dave Win's account of his life: as a schoolboy and student, discovering love, sex, and gay culture while his single mother navigates her own secret affair with another woman; as a lovely, young actor in 1970s London and on the road with an experimental theatre company; and as a married man, whose late-life romance infuses his older years with a new sense of happiness and security, even as Giles' conservative vision for England starts to poke perilous holes in that stability. This is "one of the best novelists at work today" (The Wall Street Journal) tracing a luminous line from our past to our present through one beautiful, painful, joyful, deeply observed life."--